2008
DOI: 10.1111/j.1365-2400.2007.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Management challenges of small‐scale fishing communities in a protected reef system of Veracruz, Gulf of Mexico

Abstract: Socioeconomic characterisation of fishing activities in the Veracruz Reef System National Park was used to develop a management system which balances the communityÕs livelihood, and the conservation needs of the protected area. A survey was applied to four sectors of the fishing community: the fishers, fishersÕ wives, retailers and local population. The survey determined their perceptions about: (1) fishing as a lifestyle; (2) economic alternatives;(3) perspectives about the future; (4) environment; and (5) kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Interviewed fishers informed that fish icing onboard is rare, due to the low temperatures in the harvesting season and fast transportation to the landing sites. The lack of fish conservation on board was observed by Jiménez-Badillo (2008) in Veracruz (Mexico), by Rodrigues et al (1998) for some fishers of the Bay of Babitonga (SC) and by Severo (2008) in the Beach of Pinheira (SC). Bail and Branco (2007) observed that 49% of the shrimp fishers in Praia da Penha (SC) do not use any type of conservation and 42% just use ice.…”
Section: Meanmentioning
confidence: 99%
“…Interviewed fishers informed that fish icing onboard is rare, due to the low temperatures in the harvesting season and fast transportation to the landing sites. The lack of fish conservation on board was observed by Jiménez-Badillo (2008) in Veracruz (Mexico), by Rodrigues et al (1998) for some fishers of the Bay of Babitonga (SC) and by Severo (2008) in the Beach of Pinheira (SC). Bail and Branco (2007) observed that 49% of the shrimp fishers in Praia da Penha (SC) do not use any type of conservation and 42% just use ice.…”
Section: Meanmentioning
confidence: 99%
“…Artisanal inshore reef fisheries provide a vital source of food and income for many coastal communities, and living standards in such communities are directly or indirectly linked to small-scale fisheries (Jiménez-Badillo, 2008;Kronen, 2004;Souter & Lindén, 2000). At the same time, artisanal fisheries have the potential to transform reefs in ways that compromise their ecological and economic values (Bascompte, Melián, & Sala, 2005;Carr, Anderson, & Hixo¨n, 2002;Dulvy, Freckleton, & Polunin, 2004;Hawkins & Roberts, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Policies that support effective management and natural-resource dependent livelihoods include clear rules of access and territorial rights, recognition of title/tenure, laws to support enforcement, legal mechanisms to support and guarantee meaningful participation in design and implementation, and clarity of MPA objectives [11,40,54,55,116,[118][119][120][121]. Congruence is also required between formal regulations, informal rules, and customary norms and practice [120], facilitated by policies that support the incorporation of local management systems and rules into MPA management and regulations [122,123].…”
Section: An Enabling Institutional and Organizational Environmentmentioning
confidence: 99%
“…However, fisheries benefits may be unequally shared among groups within and between communities [52,53]. Though MPAs may benefit local fisheries in the long term, in the short term compensation or alternative livelihood options need to be considered since displacement of rights to access the resource can lead to short-term hardships [50,54,55]. Diversification into alternative livelihoods may also reduce overall pressure on fisheries and the resource base [56].…”
Section: Livelihood and Community Outcomesmentioning
confidence: 99%
See 1 more Smart Citation